A brief survey of scientific results of E. A. Storozhenko - Kashin, B. S.; Korneichuk, N. P.; Ul'yanov, P. L.; Shevchuk, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We present a survey of the scientific results obtained by E. A. Storozhenko and related results of her disciples and give brief information about the seminar on the theory of functions held under her guidance.